2020
DOI: 10.3389/fpsyt.2020.00214
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Affective States and Self-Efficacy to Resist Non-Suicidal Self-Injury as Real-Time Predictors of Non-Suicidal Self-Injurious Thoughts and Behaviors

Abstract: Introduction: Although research over the past decade has resulted in significantly increased knowledge about distal risk factors for non-suicidal self-injury (NSSI), little is known about short-term (proximal) factors that predict NSSI thoughts and behaviors. Drawing on contemporaneous theories of NSSI, as well as the concept of ideation-to-action, the present study clarifies (a) real-time factors that predict NSSI thoughts and (b) the extent to which theoretically important momentary factors (i.e., negative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 78 publications
3
59
0
Order By: Relevance
“…Despite evidence that NSSI thoughts are distinct from NSSI behaviour (Kiekens et al, 2020;Nock et al, 2009), little research has considered NSSI thoughts that occur in the absence of any NSSI behaviour. In addition, despite mounting evidence that engaging in NSSI is associated with greater suicidal thoughts and behaviours (Kiekens et al, 2018;Mars et al, 2019;Ribeiro et al, 2016), questions remain regarding whether characteristics of NSSI behaviour are associated with suicidal thoughts and behaviours among community adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite evidence that NSSI thoughts are distinct from NSSI behaviour (Kiekens et al, 2020;Nock et al, 2009), little research has considered NSSI thoughts that occur in the absence of any NSSI behaviour. In addition, despite mounting evidence that engaging in NSSI is associated with greater suicidal thoughts and behaviours (Kiekens et al, 2018;Mars et al, 2019;Ribeiro et al, 2016), questions remain regarding whether characteristics of NSSI behaviour are associated with suicidal thoughts and behaviours among community adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NSSI behaviour, thoughts of engaging in NSSI are conceptualized as a component of self-injurious thoughts and behaviours (Nock, 2010). However, despite evidence that NSSI thoughts and behaviour are separable phenomena (Kiekens et al, 2020;Nock, Prinstein, & Sterba, 2009), little research has investigated adolescent NSSI thoughts in the absence of any NSSI behaviour. The ideation-to-action framework of suicidal thoughts and behaviours argues that the factors which underlie ideation may differ from those which underlie action (Klonsky & May, 2014), highlighting the need to consider NSSI thoughts as distinct from NSSI behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐efficacy to resist NSSI coincides with time since a person has self‐injured, with stronger self‐efficacy associated with a longer time since NSSI engagement (Dawkins et al, 2019a, 2019b, in press). A recent ecological momentary assessment study found that fluctuations in self‐efficacy to resist NSSI are associated with short‐term changes in NSSI thoughts, and with a lower probability of NSSI, even after controlling for NSSI thoughts and urges (Kiekens et al, 2020). Recognizing that one has the capacity to accept thoughts and urges, but not act on them, fosters self‐efficacy and may aid recovery even in the face of intense or ongoing urges to self‐injure (Kiekens et al, 2020).…”
Section: Fostering Self‐efficacymentioning
confidence: 99%
“…A recent ecological momentary assessment study found that fluctuations in self‐efficacy to resist NSSI are associated with short‐term changes in NSSI thoughts, and with a lower probability of NSSI, even after controlling for NSSI thoughts and urges (Kiekens et al, 2020). Recognizing that one has the capacity to accept thoughts and urges, but not act on them, fosters self‐efficacy and may aid recovery even in the face of intense or ongoing urges to self‐injure (Kiekens et al, 2020). At the same time, developing self‐efficacy to engage in alternative behaviors that meet the same needs as NSSI is important (Heath et al, 2016).…”
Section: Fostering Self‐efficacymentioning
confidence: 99%
“…The economic consequences of COVID-19 are predicted to be wide ranging (OECD, 2020), and thus parents and caregivers are likely also experiencing elevated stress and anxiety regarding potential job loss and financial insecurity. Given the evidence that higher-than-usual negative affect predicts subsequent NSSI thoughts and behaviour (Kiekens et al., 2020), these additional stressors are likely to impact NSSI engagement and recovery among young people with a history of NSSI. In addition, the number of life stressors (e.g., changing school, parental unemployment, major personal injury or illness, trouble with parents), in the past six months predicts the onset of self-injury among adolescents (Kaess et al., 2019).…”
Section: Impact Of Staying At Homementioning
confidence: 99%